Critical Synthesis Package: Cultural Attitudes Survey - Juanyce Deanna Taylor (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the Cultural Attitudes Survey, and (2) a copy of the Cultural Attitudes Survey instrument developed by Lynne Robins, PhD. The Cultural Attitudes Survey uses 26 items to assess medical students' comfort levels with sociocultural issues and intercultural experiences likely encountered through medical school training. The seven interpretable factors or subscales underlying the students' comfort include: Examination of Patients, Intercultural Interaction, Discussion of Race and Ethnicity, Interaction with Individuals of Diverse Sexual Orientations, Interaction with Institutional Representatives, Learning about Alternative Medicine, and Identification of Skin Conditions on People of Different Colors. The Cultural Attitudes Survey has been modified to assess sociocultural attitudes between residents and faculty members. From a social-learning perspective, faculty members and residents can use the instrument to transform their own clinical experiences in which they have encountered sociocultural challenges into training cases for medical students and colleagues. The instrument is succinct and has proven to be both reliable and valid for assessing cultural attitudes. Further analyses by gender and ethnic subgroups may be needed data to support findings due to response bias.